Stratigrafia integrata di successioni carbonatiche di mare basso del giurassico superiore–cretacico inferiore dell’appennino meridionale - Martino, Mariarosaria (2020)
Shallow-water carbonate records are often characterised by low stratigraphic resolution and poor chronostratigraphic calibration despite abundant and diversified fossil content. In particular, the Kimmeridgian – Tithonian boundary has been affected by the increase in production of pelagic carbonates linked to the rise of the eustatic curve related to the opening of the South Atlantic Ocean. Later, during the Jurassic – Cretaceous transition, the formation of epicontinental areas with restricted sea water circulation caused by the fall of sea level, promoted the evolution of endemic species. Consequently, the discovery of biostratigraphic markers still remain a task to carry on at the Jurassic-Cretaceous transition which is characterised by only low‐amplitude changes in the C isotope curve. The missing of C isotope excursions and spikes in the record of marine carbonates reveal a further difficulty to obtain accurate stratigraphic markers during this time. The early Cretaceous records, instead, are punctuated by several carbonate production crises and perturbations of the global carbon cycle (Weissert, Faraoni and Selli events). Unlike coeval northern Tethyan carbonate platforms, the Apennine platform did not drown during this time interval but responded to palaeoenvironmental and palaeoceanographic perturbations by biofacies changes that are here studied starting from the late Valanginian to the late Barremian. Possible bioevents are investigated in this PhD thesis by an integrated stratigraphy to contribute to definition and duration of the stages around the Jurassic-Cretaceous boundary and of the early Cretaceous. Multidisciplinary studies based on sedimentology, biostratigraphy, cyclo-sequence stratigraphy of shallow-water carbonates show that the bio-sedimentary system is controlled by internal and/or external processes. Understanding the role of these processes is therefore crucial to analyse how platform ecosystems respond to global environmental perturbations as well as is fundamental to perform a solid ...